Study on the enterprise system of overseas Chinese enterprises. - Li, Haixia. (2008)
The study focus on the following issues: what are the sources of growth of the overseas Chinese family enterprises? What are the institutional features of the overseas Chinese family enterprises? How do these features defer from those of western enterprises?